Facebook or LMS in Distance Education? Why University Students Prefer to Interact in Facebook Groups - Vázquez-Cano, Esteban; Díez-Arcón, Paz (International Review of Research in Open and Distributed Learning, 2021)
This article describes an investigation into the level of satisfaction among students at Spain’s National Distance Education University (UNED) regarding use of Facebook groups as an environment for learning. Based on a structural equation methodology, the research analyzed the most relevant personal and socio-educational factors that affect satisfaction. The sample consisted of 418 undergraduate and master’s degree students at UNED’s Faculty of Education; participants were consulted in three semesters between September 2019 and January 2021. The results showed that students who participated in Facebook study groups achieved better results than those who did not, and that they interacted more frequently in these groups than in UNED’s official learning management system. The main latent variables that influenced satisfaction with Facebook study groups were the perception of efficacy they elicited as a complement to distance learning by enabling greater interaction with other students, and the feeling of course companionship they provided. The absence of teacher control also influenced student satisfaction, which allowed students to focus on learning and achieving better results in tests and exams.